Study on the Effect of Different Electrode on Capacitive Deionization Microfluidic Desalination - T. Heng, J.; A. Abdulbari, Hayder (International Journal of Engineering and Technology, 2019)
Recent year, microfluidics desalination technology is on its immerging path which utilizes the domination of many apparent fluids physical properties (viscosity and surface tension) in the micro-flow systems. As compared to the traditional and commercially applied desalination methods, microfluidics overcomes most of the drawbacks such as high power consumption and low separation performance. It is believed that the flow of liquids in the micro-scaled designed structures will optimize the separation efficiency and will definitely lead to higher desalination performance. In the present work, a microfluidic desalination chip was introduced. The microfluidic desalination chip was fabricated using polydimethylsiloxane (PDMS) soft lithography method and two types of electrode were used which are titanium and aluminium. The desalination efficiency was being observed, analyzed and evaluated at the constant flow rate of 90 mL/h using capacitive deionization method. The desalination efficiency with titanium and aluminium electrode was achieved with 15% and 65%, respectively. The surface morphology of both used and unused electrodes was observed by using scanning electron microscopy (SEM). The findings in this work show that the desalination efficiency was rely on the electrode surface properties.Â Â